Active Razor Shell CaO Catalyst Synthesis for Jatropha Methyl Ester Production via Optimized Two-Step Transesterification. (12th April 2017) - Reddy, A. N. R.; Saleh, A. A.; Islam, M. S.; Hamdan, S.
Abstract : Calcium based catalysts have been studied as promising heterogeneous catalysts for production of methyl esters via transesterification; however a few were explored on catalyst synthesis with high surface area, less particle size, and Ca leaching analysis. In this work, an active Razor shell CaO with crystalline size of 87.2 nm, S B E T of 92.63 m 2 /g, pore diameters of 37.311 nm, and pore volume of 0.613 cc/g was synthesized by a green technique "calcination-hydro aeration-dehydration." Spectrographic techniques TGA/DTA, FTIR, SEM, XRD, BET&BJH, and PSA were employed for characterization and surface morphology of CaO. Two-step transesterification of Jatropha curcas oil was performed to evaluate CaO catalytic activity. A five-factor-five-level, two-block, half factorial, central composite design based response surface method was employed for experimental analysis and optimization of Jatropha methyl ester (JME) yield. The regression model adequacy ascertained thru coefficient of determination (R 2 : 95.81%). A JME yield of 98.80% was noted at C (3.10 wt.%), M (54.24 mol./mol.%), T (127.87 min), H (51.31°C), and R (612 rpm). The amount of Ca leached to JME during 1st and 4th reuse cycles was 1.43 ppm ± 0.11 and 4.25 ppm ± 0.21, respectively. Higher leaching of Ca, 6.67 ppm ± 1.09, was found from the 5th reuse cycle due to higher dispersion of Ca 2+ ; consequently JME yield reduces to 76.40%. The JME fuel properties were studied according to biodiesel standards EN 14214 and comply to use as green biodiesel.